Experimental study of the hygrothermal behaviour of External Thermal Insulation Composite Systems (ETICS) - Eva Barreira (2013)
External Thermal Insulation Composite Systems - ETICS are, now-a-days, quite common in European buildings, used both in new constructions and refurbishment. Unfortunately, ETICS can have serious problems of biological growth causing the cladding defacement. It is known that biological growth is due to high values of surface moisture content, which results mostly from surface condensation and wind-driven rain. If the drying process is not sufficiently fast, the surface moisture content remains high for longer periods and consequently increases the risk of biological growth. This paper presents the results of a detailed experimental study that was carried out by the Building Physics Laboratory of Porto University (UP), in order to assess the hygrothermal behaviour of facades covered with ETICS, namely to evaluate the influence of orientation on surface humidification, by external condensation and by wind-driven rain. A building located in UP campus, with its four facades facing the cardinal directions, was monitored during one year. The exterior surface parameters under study were temperature, long wave radiation, wind-driven rain and relative humidity. The exterior climate was also measured to evaluate surface condensation.